Application of First Order Differential Equations to Heat Transfer Analysis in Solid - SOUKSOMVANG, Phouvanh (Souphanouvong University Journal Multidisciplinary Research and Development, 2021)
Differential Equations (like Ordinary Differential Equations and Partial Differential Equations) are fundamental importance in engineering mathematics and physics because any physical laws and relations appear mathematically in the form of such equation. In this paper, first order linear homogeneous equations, first order linear non-homogeneous equations and application of the first order differential equations to the heat transfer analysis particularly in the heat conduction in solid.